2022
DOI: 10.36660/abc.20210328
|View full text |Cite
|
Sign up to set email alerts
|

Alcance das Metas de Colesterol LDL após Infarto Agudo do Miocárdio: Dados Reais do Sistema Público de Saúde da Cidade de Curitiba

Abstract: Fundamento: A redução dos níveis de colesterol LDL é a pedra angular na redução de risco, mas muitos pacientes de alto risco não estão atingindo as metas lipídicas recomendadas, mesmo em países de alta renda. Objetivo: Avaliar se os pacientes atendidos na rede pública de saúde da cidade de Curitiba estão atingindo as metas de colesterol LDL após infarto agudo do miocárdio (IAM). Métodos: Esta coorte retrospectiva explorou os dados de pacientes internados com IAM entre 2008 e 2015 em hospitais públicos da cidad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
4
0
2
Order By: Relevance
“…Statins are recommended by guidelines to intensively reduce LDL-cholesterol in people with previous manifestations of ASCVD however previous studies had shown that recommended LDL-cholesterol goals were seldom attained by Brazilian patients. 6 , 15 , 16 , 23 , 24 The findings of this study performed in a broad sample of patients from different Brazilian regions visited by CHW in both rural and urban areas, indicate that absence or inadequate statin use may explain the latter. In addition, subjects reported low use of combination therapy with ezetimibe and no use of PCSK9 inhibitors, medications that reduce not only LDL-cholesterol but prevent ASCVD events.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Statins are recommended by guidelines to intensively reduce LDL-cholesterol in people with previous manifestations of ASCVD however previous studies had shown that recommended LDL-cholesterol goals were seldom attained by Brazilian patients. 6 , 15 , 16 , 23 , 24 The findings of this study performed in a broad sample of patients from different Brazilian regions visited by CHW in both rural and urban areas, indicate that absence or inadequate statin use may explain the latter. In addition, subjects reported low use of combination therapy with ezetimibe and no use of PCSK9 inhibitors, medications that reduce not only LDL-cholesterol but prevent ASCVD events.…”
Section: Discussionmentioning
confidence: 76%
“…3 , 13 , 14 Few studies with a relatively small number of patients indicate; however, that LDL-cholesterol levels are not adequately controlled in high-risk Brazilian patients. 6 , 15 , 16 So far there is no robust and representative information on the use of statins in patients undergoing secondary prevention due to previous myocardial infarction or stroke in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Os níveis médios de LDLc foram 105 ± 38, 109 ± 39 e 110 ± 37 respectivamente com apenas 18,8% sendo considerados com níveis de LDLc adequados à categoria de risco pertencente. 292 …”
Section: Conhecimento Tratamento E Controleunclassified
“…Constituem-se, assim, um tema de ampla investigação científica, por apresentar natureza multifatorial, ou seja, por repercutir na saúde da população, nos gastos com tratamento de saúde e na identificação de medidas preventivas e reabilitadoras. Embora o número de estudos seja vasto, esses abrangem populações com faixas etárias diferentes, priorizando adultos e idosos, e, estudando os fatores de risco de forma isolada (Bernardi et al, 2022). Sendo assim, torna-se relevante investigar se há diferenças substanciais na magnitude dos fatores de risco cardiovasculares entre grupos etários diferentes.…”
Section: Introductionunclassified